A study of quality of life in children with cancer in hospital universiti sains malaysia, kelantan, Malaysia. - Goh, Chin Buan (2012)
Holistic approach not only involve optimizing anti-cancer treatment but also improving Health Related Quality of Life. PedsQL™ Cancer Module is a widely used validated and developmentally appropriate questionnaire designed to measure pediatric cancer specific HRQOL for children age 2 to 18 years. This is the first report validating and assessing children and also first proxy report in HRQOL of children treated for cancer using cancerspecific and developmentally-appropriate questionnaire for children in Malaysia. The participants were children and their caretakers with various types of cancers who received treatment in Hospital Universiti Sains Malaysia (HUSM). The PedsQL consists of 2 sets of questionnaires, which are pediatric quality of life self-report for children ages 5-12 years and parent-proxy report of child QOL questionnaire. PedsQL™ Cancer Module was culturally and linguistically validated into Malay version as recommended by MAPI Research Institute. Lingusitic validation included forward and backward translation, face and content validation and reliability test. Reliability was determined by internal consistency using Cronbach alpha and test-retest reliability using Intra-class Coefficient Efficiency. The validated Malay version PedsQL™ 3.0 Cancer Module (Malay) was administered to 107 children with cancer (for aged 5 to 18 years) and 137 parental proxies (for aged 2 to 18 years) in HUSM, Kelantan, Malaysia. Paired t-test was used to determine the mean difference between child and parental proxy HRQOL scores (except for age group 2 to 4). Multifactorial ANOVA was used to compare the mean scores of HRQOL between groups (on treatment versus completed treatment). Cronbach’s alpha coefficients ranged from 0.77 to 0.93 for children and 0.80 to 0.93 for parental proxy reports. The Intra-class correlation coefficient was between 0.88 to 0.92 for children reports and 0.86 to 0.91 for parental proxy reports. The parental-proxy HRQOL reports scored significantly lower compared to children across all age groups [68.9 (19.20) vs 73.4 (18.8)]. The mean cut-off point for domain at risk of impaired HRQOL (less than 70) was ‘Procedural Anxiety’ across all age groups (between 39 to 65.9). After adjusted for gender and diagnoses, there was also significantly lower HRQOL score between ‘ontreatment’ and ‘completed treatment’ group across most of the age groups (except parental proxy reports for 2-4 and 8-12). PedsQL 3.0 Cancer module (Malay version) was linguistically validated and comparable to original and other translated questionnaire. Administration of the questionnaire to children with cancer and their proxy revealed that parental proxy reports tend to underestimate the HRQOL of children. “Procedural Anxiety” was identified as the main HRQOL affected subscale in our children. Children on treatment generally had impaired HRQOL independent of gender and diagnoses.